Characterization of a chemically induced osteoarthritis model in zebrafish - Gongyi Xiao; Jin Qin; Huiping Yang; Qizhi Song; Ruobin Zhang; Junlan Huang; Yuexi Mou; Wen Liu; Xianding Sun; Mao Nie (Scientific Reports)
Abstract Osteoarthritis (OA) is characterized by the progressive degeneration of the synovial joint, leading to irreversible damage to articular cartilage and subchondral bone. While animal models have advanced our understanding of OA, numerous unresolved issues still remain. The zebrafish, known for its transparent body, rapid developmental, and impressive regenerative capabilities, offers substantial potential for osteoarthritis research. This study seeks to establish a new OA model utilizing the zebrafish jaw joint, acting as a supplement to traditional animal models. In the future, this model could serve as a valuable platform for delving deeper into the mechanisms of this disease, as well as for advancing drug discovery and therapeutic interventions. Leveraging the skeletal structure of zebrafish, we targeted the largest jaw joint for our research. A custom fixation device was crafted, and a microinjection system was utilized to inject mono-iodoacetate (MIA) or collagenase type II (CTII) into the joint cavity of zebrafish. Subsequent analyses included histological staining, immunohistochemistry, OA research society international (OARSI) scoring, and real-time in vivo imaging were performed at 7, 14, and 28 days post injection. Our results effectively demonstrated the presence of synovial inflammation and cartilage damage within the zebrafish mandible, affirming the feasibility of inducing OA in zebrafish. In conclusion, the local injection of chemical agents into the joint cavity of zebrafish effectively induced the occurrence of OA. Establishing the zebrafish OA model enhances the array of animal models available for OA research. Moreover, zebrafish present distinct advantages, including robust regenerative abilities, genetic editing simplicity, and efficient drug screening. Consequently, this offers a fresh avenue for investigating the pathogenesis, prevention, and potential therapeutic approaches for human OA.